Letramento literário: reflexões sobre a violência contra a mulher na literatura brasileira - uma proposta para os anos finais do ensino fundamental - Oliveira, Lorena Nogueira Costa (2024)
This project aims to develop literary literacy methods to form critical readers through the study of texts written by female authors discussing the issue of violence against women. Given the increasing gender violence rates during the pandemic, the importance of addressing this topic in the classroom and using literature as a tool for social change has become increasingly evident. The selection of works by Clarice Lispector ("The Language of the P"), Lygia Fagundes Telles ("Come See the Sunset"), and Marina Colasanti ("Yet Equally") aims to promote reflection on violence against women and patriarchal violence, following bell hooks' principles. In this context, Portuguese language classes become spaces of resistance against sexism and misogyny, contributing to students' critical development. This approach allows students not only to learn the language but also to become aware of social and gender issues in society. The theoretical basis for this work on literary literacy and literature in the school context includes Cosson, Dalvi, Gomes, Macedo, Zilberman, and Rouxel. To address issues of violence against women, Beauvoir, Tiburi, Bravo, hooks, Meneghel, and Portella were consulted. Ultimately, the aim is to prompt reflections on sexism, femicide, and female empowerment through literary literacy. Moreover, the study acknowledges the relevance of the school environment as a conducive space for social change and empowerment. Portuguese language classes are directed to serve as reflective spaces on the issue of femicide, aiming to confront patriarchy. The research was conducted at the Municipal School CAIC Misael Aguilar in Juazeiro-BA, involving 9th-grade students. The qualitative approach facilitated active student participation in the reflection and interpretation of the texts.